Accessibility and Disability at the University: Policy of Human Resources - Candido Pereira, Carlos Eduardo [UNESP]; Bizelli, Jose Luis [UNESP]; Leite, Lucia Pereira [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
This essay is part of a network investigation on public policies regarding accessibility and inclusion of people with disabilities in the Brazilian Universities. The university is unprepared to deal with the inclusive process in spite of the many specific policies for this purpose. The chosen field for the analysis was a public university in the state of Sao Paulo, and the defined methodological procedures - which involves thorough re-reading of the pertinent bibliography, interviews with university management personnel, documentary findings and data research - found great difference in the way the public and the private spheres deal with the inclusion of people with disabilities. The lack of knowledge of the specificities of the target group amplifies the challenge of the case studied, or even the ignorance of the management personnel regarding the university public workers. Bibliographic research, interviews and data findings give us this conclusion. The discussions use as basis Especial Education and Public Administration authors as well as the reviewing of normative legislations, in the case of the state of Sao Paulo. Considerations: between the public and private spheres there are great differences in dealing with the inclusion of people with disabilities. Dealing with the inclusion poses a challenge and in the case of the university, the problem increases due to the lack of knowledge of the specificities of the target group.
Keywords: Inclusion; People with Disabilities; Higher Education; University; Work; Public Policy Market